Unmasking the Mah Meri mask: A digitization journey for AR and VR. Issue 1 (1st June 2021) - Santano, Delas; Esmaeili, Human; Thwaites, Harold; Amar, Shamsul
The Mah Meri is an indigenous tribe in Malaysia, specifically located in the central region of the peninsular. As part of an ongoing research project to digitize their way of life, this article focuses on the aspects of documenting their wooden masks and statues that are carved by hand. They use these masks and statues in their animistic rituals, and each of these artefacts represents a folklore story in the Mah Meri culture and heritage. For a long time, these masks and statues have become a source of income for the Mah Meri carvers, as they get requests from collectors and enthusiasts. However, these days the craft not only faces the issue of dwindling number of carvers, but also the source of wood they use for carving the masks and statues. Thus, as part of the research in digitizing the masks and statues, we also collected the folklore stories of each artefact. Additionally, we used photogrammetry techniques to digitize the masks and statues formation process. The main idea is to create an experience that not only preserves and represents the art of the Mah Meri people, but also enables the users to interact with the carving process of the exact mask or statute. This is highly unlikely in the real world in an immersive form. In this project, we refer to this as 'Digitization of States', i.e. three-dimensional (3D) capturing of specific stages of the carving process before they are gone. The 3D-captured materials, combined with other forms of audio-visual data are used in creation of procedural and informative AR/VR experiences. To achieve this, a cross collaboration between the carvers and the researchers took place. More information about the entire process is provided in the article.